IMPLEMENTASI JARINGAN SELULER PADA KAWASAN WISATA KAMPUNG REWAKO - Zaenal Hasrul Maulana; Safaruddin (P3M STMIK Profesional Makassar, 2024)
This research aims to design a new cellular network or site in the area so that visitors and the surrounding community can use a cellular network with good quality. The method used is the drive test method to determine the quality of the network in the area. Then a cellular network design simulation was carried out using the Atoll application. From the results of the network design, testing was then carried out using point analysis in the Atoll application and the results were that the network quality in the area became better.